2010
DOI: 10.1111/j.1439-0531.2010.01633.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Placentitis in the Mare: An Update

Abstract: Contents Ascending placentitis is a common cause of premature birth, abortion and delivery of compromised, ill foals. Recent experimental models have investigated diagnostic procedures and treatment strategies in an attempt to improve live foal rate. Diagnostics such as transrectal and transabdominal ultrasonography are used to evaluate foetal well‐being and placental separation, while measurement of plasma progestins or oestrogen identifies a stressed or hypoxic foetus. Treatment is directed at stopping sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 43 publications
2
52
0
9
Order By: Relevance
“…Giles et al (1993) reported that the incidence of foetus loss in different equine breeds due to ascending bacterial placentitis (foetal death, abortion and stillbirth) reached 20%, while others quantified these losses at 10% in a sample where the majority of cases were from Thoroughbred mares (Smith et al, 2003). LeBlanc (2010) reported that placentitis affects approximately 3-7% of pregnant mares, in line with Troedsson and Zent's (2004) findings in Thoroughbred mares. But there are no references describing the incidence of foetus loss due to placentitis in SPB mares.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Giles et al (1993) reported that the incidence of foetus loss in different equine breeds due to ascending bacterial placentitis (foetal death, abortion and stillbirth) reached 20%, while others quantified these losses at 10% in a sample where the majority of cases were from Thoroughbred mares (Smith et al, 2003). LeBlanc (2010) reported that placentitis affects approximately 3-7% of pregnant mares, in line with Troedsson and Zent's (2004) findings in Thoroughbred mares. But there are no references describing the incidence of foetus loss due to placentitis in SPB mares.…”
Section: Introductionsupporting
confidence: 79%
“…One of those cited is placentitis, with a general incidence of 3-7% (LeBlanc, 2010). In recent years ultrasonography has been recognized as providing a useful technique for estimating the state of the placenta and foetus (Troedsson and Zent, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A placentite ascendente na égua é uma das principais causas de parto prematuro, aborto e nascimento de potros comprometidos (LeBlanc, 2010), sendo o Streptococcus equi, subespécie zooepidemicus, o principal agente causador . A pesquisa para se encontrarem marcadores precoces da inflamação vem sendo foco nas medicinas humana e veterinária ao longo dos anos, utilizando-se principalmente a identificação bioquímica das proteínas de fase aguda (PFA) como marcador do grau da inflamação (Crisman et al, 2008).…”
Section: Introductionunclassified
“…However, in experimentally induced placentitis caused by Streptococcus equi subsp. zooepidemicus, TMP-SMX increased the viability of foals, 2,12 suggesting that the drug reached the placenta at therapeutic concentrations. In a study of placental transfer of gentamicin and penicillin G, it was shown that the selected drugs attained therapeutic concentrations in allantoic fluid suggesting successful treatment is possible to treat the bacterial placentitis cases.…”
mentioning
confidence: 99%
“…12,14 Unlike typical cases of ascending placentitis in which transrectal examination is adequate, diagnosis of nocardioform placentitis includes ventral transabdominal ultrasound.…”
mentioning
confidence: 99%